Maximum Surgical Blood Ordering Schedule in Orthopedic Department at UNAIR Hospital January-June 2021 - Diah Puspita Rini; Alexa Surya Romansyah; Andre Triadi Desnantyo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Excessive ordering of blood components causes problems such as a lack of proper distribution of blood products between centers, increased costs, and workload of blood banks. Effective use of MSBOS will reduce the cross-match of patient blood samples and reduce unnecessary testing. This is also expected as a way to improve the quality of health services at UNAIR Hospital and reduce patient treatment costs. This study aimed to find out the MSBOS profile for orthopedic surgery at UNAIR Hospital in the period January-June 2021. This study is a cross-sectional study with a sample of orthopedic patients at UNAIR Hospital. The period was 6 months (January-June 2021). Cross-match to Transfusion Ratio (CTR), transfusion probability, and transfusion index calculations were carried out so that MSBOS could be formulated. A total of 33 units of blood were cross-matched from 21 patients in this study, whereas only 5 units of blood were transfused to 4 patients. It was found that 7 out of 8 types of surgeries had a CTR value of more than 2, a total of 6 types of surgeries had a low transfusion probability (below 30), and 6 types of surgeries had a TI below 0.5. In Total Hip Replacement (THR) and ORIF plating symphysis surgery, it is recommended that 2 units of blood be MSBOS, while for others, Group, Screen, Hold (GSH) is recommended. Further research with larger samples is needed to obtain more accurate results.